Susceptibility of native and invasive submersed plants in New Zealand to florpyrauxifen-benzyl in growth chamber exposure studies. (1st September 2022) - Howell, Andrew W.; Hofstra, Deborah E.; Heilman, Mark A.; Richardson, Robert J.
Abstract: Invasive aquatic plants constantly threaten freshwaters and associated environs globally. Water resource managers frequently seek new control tactics to combat invasive macrophytes, especially when the availability of herbicides registered for submersed plant control is limited. The synthetic auxin herbicide, florpyrauxifen-benzyl, recently registered (2018) for aquatic site applications in the United States, has shown success in controlling several invasive aquatic weeds. Studies were conducted to evaluate responses of native and invasive submersed plants to florpyrauxifen-benzyl under growth chamber conditions to provide insight on the selectivity of varying herbicide concentrations in New Zealand. Florpyrauxifen-benzyl concentrations evaluated ranged from 0.01 to 107.86 µg ai L −1, encompassing the maximum use concentration (48 µg L −1 ) for submersed plant applications. Dose–response metrics indicated the New Zealand native species watermilfoil [ Myriophyllum triphyllum Orchard] was highly sensitive to florpyrauxifen-benzyl following a 21-d static exposure, having a dry weight 50% effective concentration (EC50 ) value of 1.2 µg L −1 . The invasive species oxygen-weed [ Lagarosiphon major (Ridley) Moss] and Canadian waterweed ( Elodea canadensis Michx.) were less sensitive, with dry weight EC50 values of 35.4 and >107.86 µg L −1, respectively. Brazilian waterweed ( Egeria densa Planch.) was most tolerant to the tested concentrations, as EC50 values were not achieved. Overall, results indicate florpyrauxifen-benzyl demonstrates potential for controlling L. major, with further large-scale screening required to confirm control among field site applications. As the native species ( M. triphyllum ) was most sensitive to florpyrauxifen-benzyl compared with the invasive plant evaluated (I/N ratio indicated >31.3 times more sensitive), any targeted concentration used for invasive plant control for field applications would likely injure the native M. triphyllum plants. Future studies should investigate additional native and invasive species for management guidance and consider how exposure times influence plant response using similar florpyrauxifen-benzyl concentrations tested in the present study.